Divorced Young Adult Mothers' Experiences of Breakup: Benefits and Drawbacks. (August 2017) - Langlais, Michael R.; Anderson, Edward R.; Greene, Shannon M.
The goal of the current study is to examine the consequences of postdivorce dating breakup for young adult divorced mothers, ages 21–29. First, we hypothesized that breakup would be negatively related to maternal well-being. Second, we predicted that relationship quality would moderate this relationship. Third, we hypothesized that forming and maintaining new subsequent relationships after breakup would promote maternal well-being. Using monthly surveys completed by young adult divorced mothers over a 2-year period after divorce ( N = 51), we used hierarchical linear modeling techniques to test the changes in intercept and slope of breakup for maternal well-being. The event of breakup did not predict the changes in maternal well-being, whereas remaining single after breakup was negatively associated with depressive symptoms. Relationship quality and forming subsequent romantic relationships after breakup did not predict the changes in maternal well-being. Implications for maternal adjustment are discussed.